Multiplicity of sign-changing solutions for Kirchhoff-type equations. (September 2019) - Cassani, Daniele; Liu, Zhisu; Tarsi, Cristina; Zhang, Jianjun
Abstract: We are concerned with sign-changing solutions to nonlocal perturbation of the nonlinear Schrödinger equation in the whole R 3 . By using the method of invariant sets of descending flow, we prove the existence of multiple sign-changing solutions provided the perturbation is sufficiently small.